2019
DOI: 10.1007/s10295-018-02120-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive molecules fromNocardia: diversity, bioactivities and biosynthesis

Abstract: Nocardia spp. are catalase positive, aerobic, and non-motile Gram-positive filamentous bacteria. Many Nocarida spp. have been reported as unusual causes of diverse clinical diseases in both humans and animals. Therefore, they have been studied for a long time, primarily focusing on strain characterization, taxonomic classification of new isolates, and host pathophysiology. Currently, there are emerging interests in isolating bioactive molecules from diverse actinobacteria including Nocardia spp. and studying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 160 publications
0
30
0
Order By: Relevance
“…AD domain sequences associated with the non-Streptomyces actinobacteria, showed a prevalent distribution (>50% of relative abundance) in some samples: e.g., Mycobacterium in sample 87 and Nocardia in sample 72 (Table S5). Nocardia strains are also very rich producers of bioactive NPs [67] and have been previously isolated in Antarctic studies [68], but, to our knowledge, no compounds have been reported from Antarctic Nocardia strains (Table S5).…”
Section: Taxonomic Identity Of Nrps Genesmentioning
confidence: 99%
“…AD domain sequences associated with the non-Streptomyces actinobacteria, showed a prevalent distribution (>50% of relative abundance) in some samples: e.g., Mycobacterium in sample 87 and Nocardia in sample 72 (Table S5). Nocardia strains are also very rich producers of bioactive NPs [67] and have been previously isolated in Antarctic studies [68], but, to our knowledge, no compounds have been reported from Antarctic Nocardia strains (Table S5).…”
Section: Taxonomic Identity Of Nrps Genesmentioning
confidence: 99%
“…These bacteria have been shown to produce structurally diverse NPs with potent bioactivities. [29][30][31][32][33] The antimicrobials from Nocardia spp. and bacteriocins from Staphylococcus spp.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…and bacteriocins from Staphylococcus spp. have been summarized in recent reviews, 25,33 and thus those NPs with remarkable activities from these bacteria were highlighted. Finally, we provide a thorough compilation of the antimicrobial NPs from bacterial pathogens, Burkholderia spp., C. puniceum, Dickeya spp., E. amylovora, Nocardia spp., Photorhabdus spp., P. larvae, Pseudomonas spp., Staphylococcus spp., S. marcescens, S. mutans, Streptomyces spp., Vibrio spp., Xanthomonas spp., Xenorhabdus spp., and Yersinia ruckeri (see Table S1 in the ESI † of this article listed in alphabetical order).…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…In this review, the bacteria causing respiratory tract infections are introduced, and in the next step, the experimental methods used to recognize the cause of infections are explained. (31)(32)(33) On standard laboratory media, after incubation at 35-37°C for several days, they develop as heaped, irregular, and waxy colonies.…”
Section: Infection Epidemiology and Microbiologymentioning
confidence: 99%